MY AFRO-LATIN AMERICA: INTRODUCTION TO COSMOLOGICAL HISTORY - Pino, Julio Cesar (Journal of Al-Tamaddun, 2016)
These explorations in history are dubbed "Afro-Latin Essays" first of all because the author is himself Afro-Latin. This is a portrait of my America, much as the Franco-American historian Eugene Weber wrote of "My France." This is my America, and I do not pretend it is anyone else's. The essays collected here are the product of over thirty years of study and political activism dating back to my undergraduate days at the University of California at Los Angeles (UCLA). One conclusion I have drawn from three decades of scholarship is "no study, no political practice, and vice versa." As the author of these reflections I participated, in a modest way, in the struggles of the peoples of Latin America to gain their freedom, from my native land of Cuba to Central America to what I now consider my second patria, Brazil. I was and remain the perennial student and the workers and peasants of Latin America---black, white, indigenous, female and male---are my professors. My heritage is Afro-Latin, my subjects are Afro-Latin, and to the extent that research and imaginative insight permit, my weltanschauung is Afro-Latin.